The Effect of Areca Nut Commodity Prices and Land Area on Farmers’ Income in Sungai Undan Village, Inhil, Riau - Elisda Eriani; Hansen Rusliani (Darul Yasin Al Sys, 2026)
Although previous studies have examined areca nut farming, production, and marketing in several regions, research specifically analyzing the effect of areca nut commodity prices and land area on farmers’ income in Sungai Undan Village, Indragiri Hilir Regency, Riau, remains limited. This study aimed to analyze the influence of areca nut commodity prices and land area on farmers’ income. A quantitative approach with a descriptive-correlational survey design was employed, involving 50 areca nut farmers selected from a population of 100 farmers using the Slovin formula with a 10% margin of error. Data were collected through questionnaires, face-to-face interviews, and village documents, and were analyzed using descriptive statistics and multiple linear regression with SPSS. The findings indicate that areca nut commodity prices have a positive and significant effect on farmers’ income, whereas land area has a positive but non-significant effect. Simultaneously, both variables significantly influence farmers’ income, with an Adjusted R Square value of 0.552. These findings suggest that commodity price dynamics play a more decisive role than land ownership size in shaping farmers’ income in the study context. The study contributes to the literature on agricultural income, rural commodity trading, and Islamic economic justice by highlighting the importance of fair and transparent market mechanisms for smallholder farmers. The conclusion emphasizes the need to strengthen fairer pricing mechanisms, improve farmers’ bargaining power, and develop more transparent marketing systems to support income sustainability in rural agricultural communities.